FEMALE UNEMPLOYMENT RATE ON FERTILITY RATE IN RELATION TO REPRODUCTIVE HEALTH LAW IN THE PHILIPPINES: A MULTIVARIATE ANALYSIS (Journal of Computational Innovation and Analytics (JCIA), 2022)
The population of the Philippines continues to grow over the years, which leads to different economic concerns. The aim of this study is to determine the significance of the Reproductive Health Law and female unemployment rate on fertility rate in the country. Most studies imply a negative relationship between female unemployment rate, GNI per capita, registered marriages, and reproductive health programs on fertility rate. The result of these studies adheres to the author’s claim that there is a negative relationship among variables. A quantitative research design was used in this study. The used of multiple regression analysis examined the relationship of each explanatory variable to fertility rate based on the data gathered from 1980 to 2020. Results show that RH Law has a negative relationship on fertility rate, while unemployment rate has a positive relationship on fertility rate. This indicates that fertility rate declines because of the implementation of the RH Law that will result to slowdown the increase in population.